2017
DOI: 10.5944/ap.14.1.19262
|View full text |Cite
|
Sign up to set email alerts
|

Bienestar psicológico, personalidad y actividad física. Un estilo de vida para la vida adulta

Abstract: Practice of physical activity is increasingly important for people both as a recreational activity as a health activity. Although it is difficult to find human behaviors that do not have any influence on the health and well-being, it´s possible to show conduct that are among the most important risk factors of major health problems today such as consumption alcohol, obesity and snuff. Regular healthy physical exercise following programmes or frequent and regular autonomous activities improves mental health, aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
1
6
0
3
Order By: Relevance
“…The findings from this study confirm that young people with a preference for performing physical-sports activities in their leisure time present higher average scores in all the dimensions of wellbeing compared to those who do not perform any type of physical-sports activity. These data are congruent with those provided by other studies that have found a direct relationship between both variables (Babyak et al, 2000;Sale et al, 2000;Cantón, 2001;Chen, 2001;Penedo and Dahn, 2005;Romero et al, 2009;Greenleaf et al, 2014;Reigal et al, 2014;González-Hernández et al, 2017;McMahon et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings from this study confirm that young people with a preference for performing physical-sports activities in their leisure time present higher average scores in all the dimensions of wellbeing compared to those who do not perform any type of physical-sports activity. These data are congruent with those provided by other studies that have found a direct relationship between both variables (Babyak et al, 2000;Sale et al, 2000;Cantón, 2001;Chen, 2001;Penedo and Dahn, 2005;Romero et al, 2009;Greenleaf et al, 2014;Reigal et al, 2014;González-Hernández et al, 2017;McMahon et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Over the last two decades, the relationship between physicalsports activities and psychological wellbeing has attracted the attention of the scientific community. Numerous studies have demonstrated that a direct relationship exists between both variables (Babyak et al, 2000;Sale et al, 2000;Cantón, 2001;Chen, 2001;Romero et al, 2009;Reigal et al, 2014;González-Hernández et al, 2017). In addition, all types of physical-sports activities have been identified as favoring positive psychological wellbeing (Penedo and Dahn, 2005) regardless of the environment in which they are preformed (Lawton et al, 2017).…”
Section: Physical Sports Activities and Psychological Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation
“…Practicar actividad física cada vez es más importante, sea a nivel recreativo o como actividad de salud. Es difícil encontrar comportamientos humanos que no tengan ninguna influencia en la salud y el bienestar (González-Hernández, et al, 2017). Al analizar el bienestar psicológico en sus dimensiones y relacionar las respuestas de los mayores en la entrevista sobre la actividad física.…”
Section: Bienestar Psicológicounclassified
“…There are also studies done on lifestyle and psychology such as that by Gonzalez-Hernandez et al (2017) which found that human psychological well-being and personality are related to physical activity. In line with technology era, there are also studies done on lifestyle and cyberworld internet addiction, such as that by Shrivastava et al (2018) which found that internet addiction affected productivity and work procrastination.…”
Section: Introductionmentioning
confidence: 99%